2010
DOI: 10.1159/000317060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propofol and Isoflurane Anesthesia on the Intraocular Pressure and Hemodynamics of Pigs

Abstract: To determine the conditions under which anesthetized pigs can be used in acute noninvasive investigations of ocular hydro- and hemodynamics, the intraocular pressure (IOP) of adult pigs was recorded under the following conditions: (1) after intravenous injection of propofol plus ketamine; (2) during inhalation of isoflurane, and (3) 2 h after topical administration of bimatoprost or (4) timolol. Propofol/ketamine and isoflurane induced significant decreases in the IOP. The pulsation of the ophthalmic artery ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…16 Most of the literature suggests that isoflurane lowers IOPs; however, at least one study suggests that it increases IOP. 16,122,124,129 For example, isoflurane administration in pigs has been shown to result in a decrease in IOP from 16.5 to 14.9 mmHg (i.e., 9.7%; n ¼ 9). 16 In another study, IOP decreased when using a combination of isoflurane and remifentanil.…”
Section: Isofluranementioning
confidence: 99%
See 1 more Smart Citation
“…16 Most of the literature suggests that isoflurane lowers IOPs; however, at least one study suggests that it increases IOP. 16,122,124,129 For example, isoflurane administration in pigs has been shown to result in a decrease in IOP from 16.5 to 14.9 mmHg (i.e., 9.7%; n ¼ 9). 16 In another study, IOP decreased when using a combination of isoflurane and remifentanil.…”
Section: Isofluranementioning
confidence: 99%
“…16,122,124,129 For example, isoflurane administration in pigs has been shown to result in a decrease in IOP from 16.5 to 14.9 mmHg (i.e., 9.7%; n ¼ 9). 16 In another study, IOP decreased when using a combination of isoflurane and remifentanil. 122 In contrast, Mowafi et al reported that IOP increased with isoflurane anesthesia.…”
Section: Isofluranementioning
confidence: 99%
“…Sugar glider IOPs (12 ± 2.6 mmHg) were slightly lower than those reported for guinea pigs (16.5 ± 1.3 mmHg) using the TonoVet PLUS on “rabbit” calibration. Isoflurane has been shown to significantly decrease IOP in dogs and pigs, 27,28 thus anesthesia could have decreased IOP obtained from sugar gliders in this study. This phenomenon was also noted in koalas, as those that were conscious had IOPs greater than those induced with alfaxalone and maintained on isoflurane (15.3 ± 5.1 mmHg and 13.8 ± 3.4 mmHg, respectively) 16 .…”
Section: Discussionmentioning
confidence: 59%
“…Our results demonstrated that N 2 O did not affect IOP during 3 hours in patients under general anesthesia with sevoflurane and remifentanil. However, IOP increased at 3 hours after induction of anesthesia compared with starting point in both patients with and without N 2 O. Intraocular pressure (IOP) is known to changing at perioperative period due to anesthetic maneuvers [3] [17], anesthetic agents [4] [18]- [21], and patient's position [22]- [27] and hemodynamics [28]. Tracheal intubation [29], succinylcholine [5]- [7], inhalational anesthesia [1] [2] [8], and nitrous oxide (N 2 O) [21] may influence IOP.…”
Section: Discussionmentioning
confidence: 99%